Electromagnetic and electrical methods applied to mapping coked coal – A case study from the Bowen Basin, Eastern Australia. Issue 1 (1st December 2019) - Lowe, Jonathan; Reid, James; Battig, Eric; Napier, Scott; Eremenco, Dan
Summary: In coal mining it is important to know if localised areas of coal have been rendered worthless through direct contact with volcanic intrusions. To avoid dilution, accurate coked coal boundaries are traditionally mapped by drilling. BHP has made significant strides in applying geophysical methods to add value at its coal operations. With respect to the mapping of coked coal BHP have tried a suite of electromagnetic and electrical methods; enjoying success at improving the resolution of coked coal boundaries with significant implications on the amount of drilling required. Recent trials of moving loop and airborne transient electromagnetic (TEM), Sub-audio magnetic (SAM), electrical resistivity imaging (ERI) and induced polarisation (IP) have encouraged the company to ramp up the inclusion of more TEM in its 5-year operational plans. Unconstrained 1D inversion of moving loop TEM data correlated well to drilled intersections of coked coal. This enabled an improved coked coal boundary to be mapped. An interesting observation is contrary conductivity sections obtained from moving loop TEM and ERI, with the latter method failing to identify the strong conductive layer mapped in both TEM and drilling. Possible conductivity anisotropy of the coked coal or the overlying sediments is being considered as a likely explanation for the failure of ERI to map the coked coal. Inversion of SAM TFEM data partially worked to map the coked coal but only when constrained by the TEM inversion results. The signal to noise ratio in the IP data proved to render the data uninterpretable, suggesting that the coked coal is not chargeable, with the graphite being in massive rather than disseminated form. It is concluded that moving loop TEM and helicopter TEM both efficiently map coked coal sufficiently to target reduced drilling programs. Hence, where scales are appropriate, helicopter surveying is ideal to maximise efficiency without compromising resolution or results.